Russian literature in the symphony of European cultures (International scientific conference “Russian literature and its interconnection with other national European literatures”, Greece, Athens, February 22-23, 2018) (Proceedings of Southern Federal University. Philology, 2018)
L.V. Tabachenko CHRONICLES